Transient cerebral ischaemic attacks related to egg consumption - Ellis, M. E. (1981)
A 58-year-old man is described who suffered transient cerebral ischaemic attacks when on a diet containing a large number of eggs. When the egg content and, therefore, the cholesterol content of the diet was reduced the attacks stopped. It was concluded that the variations in his cholesterol intake and in his serum cholesterol, which remained normal or near normal throughout, are relevant to the aetiology of his episodes of cerebral ischaemia and that further study of techniques designed to alter the cholesterol intake and the cholesterol level in patients with such attacks may be useful.